2023
DOI: 10.3390/biomedicines11041180
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a Model to Study Retinoic Acid Signaling in Development and Disease

Abstract: Retinoic acid (RA) is a metabolite of vitamin A (retinol) that plays various roles in development to influence differentiation, patterning, and organogenesis. RA also serves as a crucial homeostatic regulator in adult tissues. The role of RA and its associated pathways are well conserved from zebrafish to humans in both development and disease. This makes the zebrafish a natural model for further interrogation into the functions of RA and RA-associated maladies for the sake of basic research, as well as human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 251 publications
0
0
0
Order By: Relevance
“…Previous studies have suggested that atRA plays an important regulatory role in vertebrate development and that the production of a small amount of atRA is necessary to maintain normal vertebrate development . In the present study, the ontogeny, tissue structure, and function of marine medaka in the LL group were not significantly affected, indicating that under normal light, moderate RAL produced by algal cells was transmitted and transformed from the food chain and that atRA did not cause toxic damage to the fish.…”
Section: Discussioncontrasting
confidence: 49%
“…Previous studies have suggested that atRA plays an important regulatory role in vertebrate development and that the production of a small amount of atRA is necessary to maintain normal vertebrate development . In the present study, the ontogeny, tissue structure, and function of marine medaka in the LL group were not significantly affected, indicating that under normal light, moderate RAL produced by algal cells was transmitted and transformed from the food chain and that atRA did not cause toxic damage to the fish.…”
Section: Discussioncontrasting
confidence: 49%